THE SECOND WORLD WAR AS A RESULT OF THE CRISIS OF INTERNATIONAL RELATIONS IN THE 20-30s OF THE XX CENTURY - G. Rykun; T. Plohotnjuk (Гуманитарные и юридические исследования)
The article traces the dynamics of the development of crisis trends, on the one hand, within the capitalist world, conditioned by the results of the First World War and the conclusion of the Versailles Peace Treaty, on the other, between the capitalist powers and the Soviet state. Against this background, the revanchist aspirations of Germany during the Weimar Republic are shown, the process of the formation of the National Socialist regime in the Third Reich, which dragged humanity into the Second World War, is revealed. The leading powers of the capitalist world, in their striving for world domination, expanding the markets for raw materials and sales and preserving the world order established by them, made unsuccessful attempts to isolate the USSR from participating in solving major international problems and reducing its foreign policy activity, primarily in supporting national liberation movements and elimination of the world colonial system. Encouraged by radical ultra-right political forces that represented large industrial monopolies in governments, the Western powers intended to expand their possessions at the expense of the German Afro-Asian colonies, but these plans also turned out to be unrealizable. Germany, humiliated and limited in action by the requirements of the Treaty of Versailles, was not only able to defend its international interests, but also to designate claims to expand living space for the Aryans. In the end, the West, divided into two opposing blocs, decided to use the tough foreign policy course of the German leadership against the Soviet Union. To this end, it persistently pursued a policy of appeasing German militarism and ignored numerous Soviet initiatives aimed at creating a collective security system in Europe. For the reasons set out above, the West was unable to give an objective assessment of the proposals of the Soviet leadership, thereby facilitating the unleashing of the world's largest military conflict in the history of mankind by fascist Germany.